Structural integrity of aortic scaffolds decellularized by sonication decellularization system - , Aqilah Hazwani; Sha'ban, Munirah; Azhim, Azran (Institute of Electrical and Electronics Engineers Inc., 2019)
Sonication decellularization technique has shown effectiveness to remove all the cellular components by the disruption of the cell membranes and removal of the cell debris to prepare the bioscaffolds. However, it is important to confirm whether this technique does not have a detrimental effect on elastin and collagen in bioscaffolds. The objectives of this study are to evaluate the structural integrity of bioscaffolds using histological staining and quantitatively collagen and elastin measurement. Aortic tissues were sonicated in 0.1% SDS for 10 hours at the frequency of 170 kHz with the power output of 15W and washed in Phosphate Buffer Solution (PBS) for 5 days. Then the sonicated aortic tissues were evaluated by Hematoxylin & Eosin (H&E) staining for cell removal analysis, Verhoeff-van Gieson (VVG) staining for visualizing elastin and Picrosirius Red (PSR) staining for visualizing collagen. The collagen and elastic fibres were semi-quantified by ImageJ software. The results showed that sonication decellularization system can remove all the cellular components while maintaining the structural integrity of elastin and collagen on bioscaffolds. This study indicates that sonication decellularization system could remove all cellular components and maintain the structure of the extracellular matrix.